Hubungan Tingkat Kecemasan dengan Kualitas Tidur pada Mahasiswa Baru Luar Pulau Jawa Universitas Jember - Siti Hotijah; Erti Ikhtiarini Dewi; Enggal Hadi Kurniyawan (Pustaka Kesehatan, 2021)
New students have anxiety because of new social and cultural conditions. Excessive anxiety will make it difficult for a person to start sleeping, so it can cause bad sleep habits. The purpose of the study was to analyze the relationship between anxiety levels and sleep quality in new students outside Java. The study design used correlative research with a cross-sectional approach and used the total sampling technique for 103 respondents. Data collection used the Zung Self Rating Anxiety Scale (ZRAS) questionnaire and the Pittsburgh sleep quality index (PSQI). Data analysis using the Spearman’s Correlation test with a significance level of 0.05. The results showed that the respondents who had the most moderate anxiety were 69 people (67.0%), and those who had poor sleep quality were 91 people (88.3%). There is a significant relationship between anxiety and sleep quality in new students outside Java (p-value 0,000; r = 0.453), which has a positive relationship or the higher the level of anxiety, the worse the quality of sleep. New students must be able to control anxiety experienced not to affect the quality of their sleep.